Knowledge and Practice of Dental Students and Dentists Regarding Infection Control Protocols in Isfahan, Iran - Mahsa Barzegar Ghahfarokhi; Maryam Zare Jahromi; Parisa Ranjbarian; Sadaf Mahmoudi (Islamic Azad University, 2023)
Background and Aim: Transmission of infectious agents may occur in dental practice. This study aimed to evaluate and compare the knowledge and practice of general dentists, dental specialists, postgraduate students, and undergraduate 5th and 6th year dental students about infection control and prevention of cross-contamination in dental office.   Materials and Methods: A total of 155 dental specialists, general dentists, and postgraduate and undergraduate 5th and 6th year dental students participated in this cross-sectional study. The self-administered questionnaire was composed of 2 parts (knowledge and practice). Data were analyzed by the Kruskal-Wallis, and Mann-Whitney tests, one-way ANOVA, t-test and Bonferroni test (alpha =0.05). Results: No significant difference was found in knowledge about the hepatitis B virus (HBV) and human immunodeficiency virus (HIV)/AIDS transmission, wearing a mask, and use of protective glasses, shields or gown for each patient, among the participants. A significant difference was found in the practice of study groups regarding the use of protective glasses, shields or gown (P=0.003). Conclusion: In general, the knowledge of participants about infection control was poor; however, their practice was different and there is a need for further education to enhance the knowledge of dental healthcare providers about infection control.